Myeloproliferative neoplasm patient symptom burden and quality of life: Evidence of significant impairment compared to controls. Issue 10 (10th September 2015) - Anderson, Lesley A.; James, Glen; Duncombe, Andrew S.; Mesa, Ruben; Scherber, Robyn; Dueck, Amylou C.; de Vocht, Frank; Clarke, Mike; McMullin, Mary F.
<x xml:space="preserve">Abstract</x> The myeloproliferative neoplasms (MPN) including polycythaemia vera (PV), essential thrombocythaemia and primary myelofibrosis (PMF) are rare diseases contributing to significant morbidity. Symptom management is a prime treatment objective but current symptom assessment tools have not been validated compared to the general population. The MPN‐symptom assessment form (MPN‐SAF), a reliable and validated clinical tool to assess MPN symptom burden, was administered to MPN patients (n = 106) and, for the first time, population controls (n = 124) as part of a UK case–control study. Mean symptom scores were compared between patients and controls adjusting for potential confounders. Mean patient scores were compared to data collected by the Mayo Clinic, USA on 1, 446 international MPN patients to determine patient group representativeness. MPN patients had significantly higher mean scores than controls for 25 of the 26 symptoms measured (P < 0.05); fatigue was the most common symptom (92.4% and 78.1%, respectively). Female MPN patients suffered worse symptom burden than male patients (P < 0.001) and substantially worse burden than female controls (P < 0.001). Compared to the Mayo clinic patients, MPN‐UK patients reported similar symptom burden but lower satiety (P = 0.046). Patients with PMF reported the worst symptom burden (88.3%); significantly higher than PV patients (P < 0.001). For the first time we report quality of life was worse in MPN‐UK patients compared with controls (P < 0.001). Am. J. Hematol. 90:864–870, 2015. © 2015 Wiley Periodicals, Inc.